The Impact of Social Media on Women-Owned Start-Ups in Kalyana Karnataka Region - Altaf Hussain; Mallikarjun Biradar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
This study examines the impact of social media on women-owned start-ups in the Kalyana Karnataka region, focusing on how platforms like Facebook, Instagram, and WhatsApp enable entrepreneurs to overcome traditional barriers. Social media offers women business owners affordable tools for marketing, customer engagement, and brand building, essential in an economically and socially challenged region. The research, based on surveys and interviews, reveals that social media significantly contributes to the growth and visibility of these start-ups, though challenges such as digital literacy and access to technology persist. The study highlights the need for targeted training and support to help women entrepreneurs fully leverage social media for business success and regional economic development.